HIRDLS instrument radiometric calibration black body targets - Hepplewhite, C; Watkins, R; Row, F; Barnett, J; Peters, D; Palmer, C; Wolfenden, R; Djotni, K; Arter, P (2003)
The pre-launch calibration of the HIRDLS instrument took place in a dedicated facility at the University of Oxford. One aspect of this calibration was the determination of the response of the instrument to black body radiation. This was achieved with the use of purpose built full aperture black body targets which were mounted in the vacuum chamber together with all of the calibration equipment. Especial attention was placed on the absolute knowledge of the emission from these targets. This was done through a combination of thermometric sensor calibration traceable to the International Temperature Standard (ITS-90), surface emission measurements, cavity design and modelling and controlling the stray light sources in the vacuum chamber. This paper describes the design requirements, implementation and performance achieved.